PTH-052 Microscopic Colitis Is Expensive To Diagnose: An Analysis Of The Utility Of Random Colonic Biopsies. (4th June 2013) - Pannick, S; Chaggar, S; Lunn, A Dehn; Beveridge, I; Monahan, K; Sundaram, K; Collins, C; Mawdsley, J
Abstract : Introduction: Microscopic colitis is reported in up to 9.5% of patients with watery diarrhoea, and in almost 20% of those older than 70 1 . The Joint Advisory Group on GI Endoscopy mandates diagnostic colorectal biopsies in patients with persistent diarrhoea. However, the Royal College of Pathologists advises that biopsies be taken only in the "correct clinical setting… usually in a middle-aged or elderly (often female) patient" 2 . We examined our local incidence of microscopic colitis and the cost of universal biopsies, and sought to identify factors that could be used to reduce the number of biopsies required. Methods: We performed a retrospective analysis of patients investigated for diarrhoea at West Middlesex University Hospital between 1/1/2011 and 31/12/2012, where colonic biopsies were taken to exclude microscopic colitis. The patient cohort, and their endoscopic and histological findings, were drawn from the hospital's electronic medical records. Patients whose biopsies were taken for inflammatory bowel disease assessment were excluded. Those patients with a new diagnosis of microscopic colitis were identified. The estimated cost of processing 4 colonic biopsies was £55. Results: 616 patients were identified who underwent biopsies to exclude microscopic colitis during the study period. The mean number of biopsies per patient was 3.1. A total of 2056 diagnostic colonoscopies were performed in our unit during this interval; biopsies for this indication were therefore required in 30% of cases. The cost of these biopsies was around £26, 700. 9 cases of microscopic colitis were identified (median age 58; interquartile range 47.5–76.5; 3 males and 6 females), with an overall incidence of 1.5%. Incidence increased with age (see table). There were no significant differences between the patients with microscopic colitis and those with other diagnoses in terms of sex or number of biopsies. Conclusion: Biopsies for this indication are required in a high percentage of diagnostic colonoscopies, with significant resultant costs (£13, 300 per annum). Our local incidence of microscopic colitis is far lower than that published in the literature, suggesting we may be over-biopsying. We could not justify restricting biopsies to female patients, but a minimum age criterion might be appropriate. Disclosure of Interest: None Declared. References: Olesen et al. Microscopic colitis: a common diarrhoeal disease. Gut 2004; 53:346–350. Howat et al. Histopathology and cytopathology of limited or no clinical value . Royal College of Pathologists. Report number: 2, 2005.